Urgensi Pendidikan Praktik Berkuda Dan Memanah Dalam Meningkatkan Kecerdasan Emosional Santri Di PPTQ Qoryatul Qur’an - Muhammad Ikhsannudin; Joko Sarjono; M. Fatchurrohman (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
Furusiyah or equestrian sport is the ability to ride a horse and control it wherever the horse moves or runs. In general, the meaning is the science of dexterity in playing weapons on a horse or without a horse. This knowledge is considered a natural classic sport and has been very popular with Arab people since ancient times until now. Because horse riding was very important to the Arabs they taught their children from an early age to practice horseback riding and archery. In the history of the hadith that Rasulullah Shallallahu Alaihi Wasallam once raced a horse and competed with other horses. He once rode a black mare and then spurred her with both legs to say that this horse was running very fast. The person who first taught the science of furusia was Nabiyullah Ismail Alaihissalam at that time horses were wild like other wild animals. Then Allah tamed the horse and it could be ridden by Prophet Ismail Alaihissalam. Because of the diversity of horses, said Syarif Ahmad Al Hamawi in his book Annafhatul Miskiyah fii Sinaatil Furusiyah, he said, "Know that the problems with horses are very diverse that no one can know or go beyond their ends and limits because every horse of any kind has its own characteristics and gaps. each other's defects." Horse riding and archery extracurriculars at PPTQ Qoryatul Quran are one of the extras that can improve the quality of the students' memorization. Horse riding can also improve body health and physical strength. Horse riding and archery can also increase the focus of students in memorizing and learning general subjects in class.